The Effect of Service Quality on Customer Satisfaction at The Kampoeng Nelayan Restaurant Sapolohe Bulukumba - Hasni Agustina Halim; Muh. Nasrullah; Didin Halim; Aris Baharuddin; Andi Muhammad Rivai (Fakultas Ilmu Sosial dan Hukum, 2024)
This study aims to determine the Effect of Service Quality on Customer Satisfaction at the Kampoeng Nelayan Restaurant Sapolohe Bulukumba. Data collection techniques through, observation, questionnaires, and documentation. The data obtained are processed using quantitative methods of associative descriptive research type. The samples used in this study were 100 customers who had visited Kampoeng Nelayan Restaurant Sapolohe Bulukumba. Data processing uses the SPSS 24 application which consists of validity and reliability tests, descriptive data analysis techniques and inferential analysis. The results showed that the Quality of Service and Customer Satisfaction of Kampoeng Nelayan Restaurant Sapolohe Bulukumba had a significant influence. This is evidenced based on the results of data analysis obtained a linear regression equation of Y = 7.440 + 0.772X with a constant value of 7.440 and a regression coefficient value of 0.772 which is a positive value, meaning that the quality of service has a positive effect on customer satisfaction at the Kampoeng Nelayan Restaurant Sapolohe Bulukumba.